Representations of Book Culture in Eighteenth-Century English Imaginative Writing - Maciulewicz, Joanna (New Directions in Book History, 2018)
This book is a contribution to the new field of literary studies which is informed by book history and takes interest in the intersection of the ideal and material aspects of literature. It studies the ways eighteenth-century English novels, plays and poems illustrated the changes which the growth of literacy, the proliferation of writing and the emergence of print marketplace made in the social and cultural life of Britain and demonstrated the contingency of the emerging criticism on the technological and economic conditions of book production. The first part focusses on the representation of the tensions created by the emergence of literate society and on the hopes and fears awoken by the expansion of the cultural public sphere caused by the proliferation of print. The second part explores the contribution of literature to the shaping of the roles of authors, readers and patrons in the field of literary production.